PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PEGAWAI - Moeljahwati, Endah; Suharto, Suharto; Subroto, Agus (Manajemen & Bisnis Jurnal, 2020)
The purpose of this study was to analyze the influence of organizational culture and work motivation on job satisfaction and employee performance. this type of research is explanatory research. The sample in this study was 103 employees. The analytical tool used is path analysis. Based on the analysis of evidence that organizational culture and work motivation affect job satisfaction, organizational culture, motivation and job satisfaction affect employee performance. Job satisfaction can mediate the influence of organizational culture and work motivation on employee performance. In order to improve employee performance, agencies need to create a good organizational culture that is applied to the ability to complete work, besides that employees need to be more motivated by established policies such as creating a conducive work environment, providing supporting facilities and facilities, and taking more into account forms of appreciation. for employment.